1994
DOI: 10.1007/bf01447080
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of methane conversion by a dinitrogen microwave plasma

Abstract: Conversion of CH~ with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…react with N 2 + , N + , N( 4 S) to form the NH radicals as follows [1,2]. Ion reactions (20) with high rate constant are the major reactions.…”
Section: Excited Dissociation Direct Ionization Of Ch 4 and Formatiomentioning
confidence: 99%
See 3 more Smart Citations
“…react with N 2 + , N + , N( 4 S) to form the NH radicals as follows [1,2]. Ion reactions (20) with high rate constant are the major reactions.…”
Section: Excited Dissociation Direct Ionization Of Ch 4 and Formatiomentioning
confidence: 99%
“…The excited methane S 1 (9.6 and 10.4 eV) and S 2 (11.7 eV),which are formed by the electron-methane collisions, are so unstable that rapidly dissociate into radicals such as CH 3 , CH 2 , CH, C. The plasma reactions are as follows [1][2][3]:…”
Section: Excited Dissociation Direct Ionization Of Ch 4 and Formatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Atmospheric pressure DBD experiments are limited to those reported by Oumghar et al [18,19] who reported C 2 H 2 , C 2 H 4 , C 2 H 6 , HCN and NH 3 to be the most dominant products formed in CH 4 /N 2 plasma. Thus, to date, a wide variety of experiments using discharges to simulate Titan's atmosphere have been reported but the results of such experiments are conflictory in both the product species observed and the chemical synthesis observed.…”
Section: Introductionmentioning
confidence: 95%